Research on LoRa network security schemes based on RF fingerprint - Yu JIANG; Siqing CHEN; Wen SUN (物联网学报)
Long range radio (LoRa) is widely used in the IoT due to its advantages of long distance and low power consumption.However, LoRa network has no reliable security scheme currently, making it unable to guarantee the communication security.Therefore, based on the uniqueness and tamper-resistance of radio frequency fingerprint, it was proposed to receive radio frequency signals of the LoRa end nodes which requested access, extract the fingerprints from them, mark it and match with the customized multi-scale security rules according to demands to decide whether the identities of the LoRa end nodes were safe, taking security measures accordingly.Based on this, original LoRa gateway and LoRa network architecture were improved, new workflows were designed, and two LoRa network security schemes were proposed.The two LoRa network security schemes were proposed which implement identity authentication and access control of the LoRa end nodes from the physical layer.It is only needed to improve the original LoRa gateway in the LoRa network architecture and its workflow, which adds new security measures and guarantees for LoRa applications on the basis of not affecting the original LoRaWAN security mechanism, with no need to modify a huge number of LoRa end nodes.The security schemes proposed have high practical value.